Prambors Radio Strategy Optimization: Expanding Broadcast Covering to Reach the Target Audience of Young People - MOERFIQIN, Lucky Ali; RONDA, Andi Mirza; SERAN, Alexander (International Journal of Environmental, Sustainability, and Social Science, 2024)
In today's very tight competition in radio media, especially in big cities like Jakarta, radio stations compete to dominate the listener segment and optimize revenue from advertising. However, Law Number 32 of 2002 concerning Broadcasting sets limits on the reach of local radio broadcasts, limiting the ability of radio stations to reach a limited area with listeners. This article discusses the strategic efforts of PT Radionet Cipta Karya (RCK), a holding company, as the owner of Prambors radio, to focus on increasing the number of listeners without violating applicable regulations. The research uses qualitative analysis methods and a case study approach, with interviews with the Directors and Manager of Prambors radio as the main source. The Mediamorphosis Theory by Roger Fidler (1997) was adopted in this research by highlighting media transformation as a result of the interaction of interests, political pressure, and technological and social innovation. The research results show that since 2000, Prambors radio adopted networked radio broadcasts and broadcast centralization in 2009/2010 succeeded in expanding its reach to several cities and converging with social media. The use of streaming radio also opens up access to broadcasts throughout the world for listeners with an internet connection.